Attitudes, Beliefs and knowledge of teecherz furniture male workers towards voluntary consoling and testing for HIV infection - Makomeke, Chipochedenga; Nyamakura, Rudo; Chitura, Miriam; Makomeke, Patience Chido (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Scaling up Voluntary Counseling and Testing (VCT) and treatment is a key priority in our globalresponse to the epidemic. In the context of a growing number of strategies designed to achieve thistreatment optimization, there is an urgent need for alternate delivery systems to increase access toand utilization of HIV counseling and testing facilities, the first point in the treatment cascade. Data,from the local industrial area Teecherz Furniture in Granite side, Harare, Zimbabwe supports anemerging body of literature that suggests that mobile VCT approaches, embedded in communitycontexts, are capable of reaching target groups thus far missed through the predominant healthfacility-based HIV testing approaches that currently exist. Roy’s adaptation model guided this study.The purpose of this study was to determine the attitudes, beliefs and knowledge of TeecherzFurnishers male workers towards voluntary counseling and testing for HIV. A descriptive studydesign was used. A simple random sampling of 30 participants was used. Data was collected usingface to face interviews guided by a questionnaire. In terms of attitudes, 13 (43.3%) participantsshowed positive attitudes towards VCT by stating that they would make future decisions about theirsexuality. Nineteen (63.3%) believed that VCT was leading to an increase in divorce rates. In termsof knowledge, 19 (63.3%) did not know what VCT is. The respondents of this study showed that theyhave the knowledge on both disease and the VCT HIV programme but mainly feared the issue ofstigma and discrimination. The study therefore brought out the fact that knowledge does notnecessarily influence attitude but there are several factors like family and friends support that mayhinder one from making the decision. Based on these results, it is strongly recommended thatTeecherz furnishers should continue mobilizing employees to go for VCT.